"Open‐Mouth" Mesoporous Hollow Micro/Nano Coatings Based on POSS/PDMS: Fabrication, Mechanisms, and Anti‐Icing Performance. (27th September 2018) - Yin, Yuan; Liu, Meihua; Wei, Wei; Zhang, Yifan; Gutowski, Voytek; Zhang, Wanxi; Deng, Pengyang
Abstract: A simple spray approach for fabricating unique micro–nano polyhedral oligomeric silsesquioxane/polydimethylsiloxane (POSS/PDMS) composite coatings decorated with 3D " opened‐mouth " hollow structures is reported. The structures are formed by a template‐free self‐assembly of cuboidal POSS precursors driven by room‐temperature aerosol‐assisted process. A three‐stage mechanism is proposed to explain the formation of the structures. The morphology and performance of the coatings are controlled via the type of the carrier liquid, the content of crystalline nanoparticles (POSS), the presence of ligands, and processing temperature. Mechanically stable micro‐ or micro–nano " open‐mouth " spherical or cylindrical structures with excellent super‐hydrophobic and anti‐icing properties are formed when POSS content exceeds 5%. Such spatial geometry of interphase‐embedded hollow structures incorporates effective heat‐transfer barrier, drastically reduces surface wettability and ice adhesion, which are quantified by water freezing temperature lowered to −26.3 °C and ice adhesion to 86 kPa. Abstract : A simple spray approach for fabricating unique micro–nano polyhedral oligomeric silsesquioxane/polydimethylsiloxane (POSS/PDMS) composite coatings decorated with 3D open‐mouth hollow structures is reported. The formation of the structures is explained by a proposed three‐stage mechanism. The morphology and performance of the coatings are tuned. The coatings decorated by mesoporous hollow micro–nano spheres with open‐mouth structure exhibit excellent super‐hydrophobic and anti‐icing properties.